Effect Calcium Carbonat (CaCO3) Addition on Free Fatty Acid Content of Restored Palm Oil Fruit - Simatupang, Ghana; Mondamina, Novelita; Oktavia, Listiana (Jurnal Penelitian Kelapa Sawit, 2021)
Free Fatty Acid (FFA) is one of the important parameters to determine CPO (Crude Palm Oil) quality. The restoration of palm oil allows the significant increment in the FFA content which leads to the reduction of CPO quality and declining the CPO price. Therefore, it needs the additional treatment to inhibit the increment of FFA content on the restored plam fruit. The purpose of this study is to investigate the effect of Calcium Carbonate (CaCO3) addition to the FFA content in restored palm fruit. The CaCO3 was sprayed evenly to the surface of restored palm fruitlets. The CaCO3 solution used for this treatment was 300 g/l, 350 g/l and, 400 g/l. The fruitlets were restored at 15, 23, and 28 hours. Two types of palm fruitlets used were the normal fruitlet and the surface-wounded fruitlets. The FFA was extracted by soxhlet method, while FFA determination was conducted by titration technique. The Addition of CaCO3 was observed effective to decrease FFA content on normal fruitlets with the optimum CaCO3 concentration to reduce FFA content was of 400 g/l. The FFA reduction effectivity was 39.08%, 24.29% and 19,04 for 18 h, 23 h and 28 h restored time respectively. The addition of CaCO3 was observed to be in-effective to decrease the FFA content to the surface-wounded restored palm fruitlets. This research can trigger the more advance research for improvement of CPO production that leads to the improved CPO quality.